The Pivotal Role of Guanxi for Economic Intelligence in the People’s Republic of China - Milliot, Eric (Management international / International Management / Gestiòn Internacional, 2016)
Economic intelligence can be defined as a system of learning (logic of knowledge) and lobbying (logic of influence), largely based on access to information and interpersonal relationships. In the West, learning and lobbying are managed simultaneously, sequentially or separately. Can these systems, however, be developed in the same ways in Far Eastern countries, where messages are generally implicit and relations are usually gregarious? In particular, does knowledge depend on influence in these countries?Using the People’s Republic of China as an example, and based upon a survey of 353 people, the work in this article illustrates the need for adapting economic intelligence to international operations, and underlines the relevance of guanxi in building such a system in this country.